THE CORRELATION OF INVESTMENT ATTRACTIVENESS AND INNOVATIVE MODEL OF REGION DEVELOPMENT - Leshchynskyi V.P. (Pressing Problems of Public Administration, 2016)
Questions are examined related to the investment attractiveness of regions. This description of innovative model of development of economy of country.